Improvement of Methods for Analysis of Product Resource-Ability - K. N. Malovik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
An analysis of  an actual situation with the problem concerning estimation of product resource-ability has been made in the paper. The paper considers development of methods in respect of probability theory of extreme values and its application for estimation of resource characteristics. An approach for determination of product resource-ability which is based on material yield stress and entropy criteria of product degradation has been proposed in the paper.